Stability of Dielectric Insulation System in GSUT Transformer of Pertamina Geothermal Energy Lahendong: A Diagnostic Approach Based on DFR (Dielectric Frequency Response) - Sianipar, Niko Ardiansa; Nurhayati, Titik; Supari, Supari (Transpublika Publisher, 2025)
Generator Step-Up Transformer (GSUT) is a vital component in the power system that serves to raise the voltage level before the transmission process. The operational reliability of the transformer is highly dependent on the condition of the dielectric insulation system which consists of mineral oil and insulating paper. A decrease in the quality of the insulation system can have a significant impact on the performance and operational life of the transformer. This study aims to analyze the results of Dielectric Frequency Response (DFR) testing on the GSUT Unit 6 Transformer at PGE Lahendong to evaluate the moisture content in insulating paper and the conductivity of transformer oil based on the IEC 60422 and IEC 61620 standard references. The test results based on the dissipation factor (DF) graph show that the moisture content in the insulating paper is 0.9% (dry category) and the oil conductivity is 1 fS/m, which indicates that the condition of the insulation system is still good with an estimated remaining operational life of up to 70 years by calculating the ratio between the average operating temperature value of the transformer and its dielectric rate (Dp.t). However, electromagnetic interference or bushing contamination can cause negative dissipation factor (DF) values, leading to invalid measurements. Therefore, DFR testing using the OMICRON DIRANA device proved effective in monitoring the condition of the dielectric insulation system and providing an accurate estimation of the remaining insulation life, as well as supporting the implementation of predictive maintenance strategies in power transformers.